If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5y+8-4y=3y-12
We move all terms to the left:
5y+8-4y-(3y-12)=0
We add all the numbers together, and all the variables
y-(3y-12)+8=0
We get rid of parentheses
y-3y+12+8=0
We add all the numbers together, and all the variables
-2y+20=0
We move all terms containing y to the left, all other terms to the right
-2y=-20
y=-20/-2
y=+10
| 17+13s=14s | | 11c+13+13=-16+17c | | -5=2x-3(x-2) | | -10u-20=-12u+14 | | 10-7z=-8-5z | | 2d-6=d | | -5x-4(-2x-2)=-10 | | 1/2(t-12)=4 | | h-10=10-9h+10 | | -20=-4/7v | | 6+u/2=-2 | | 4r-10=r+8 | | 4w-7=-3 | | 2-10v=-9v+3 | | 2x+4(-x-2)=-30 | | -8g-2=10-10g | | 5y-12=28y= | | -3b=6-b | | 31=u/2+15 | | -7g+9=-4g | | 3w=2w+5 | | -7x+5(4x-4)=45 | | y/5-11=10 | | 53 =10q | | 2f−6=4f | | 6m+10=22m= | | 9+2k=k | | 6/11=y/12 | | 8b=5b-20 | | 5-8y=-7y | | 4x^2-7x+4=2x+2 | | 7x-3(4x-3)=-36 |